HUBUNGAN AIR TANAMAN Acacia mangium Willd. DI HUTAN TANAMAN, PERUM PERHUTANI BOGOR WATER PLANT RELATIONSHIP OF Acacia mangium IN PERUM PERHUTANI FOREST, BOGOR - N. Fitri Hariyati; D. Murdiyarso (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2004)
Abstract is available in the full text (pdf format)